Time as an employment relationship element (comments under art. 22 § 1 of the Labour Code) - Driczinski, Sławomir (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
In the publication the author took up the subject of the time concept used in Article 22 § 1 of the Labour Code. The study analyses the role and legitimacy of inserting the term concerning the working time in Article 22 § 1 of the Labour Code. This concerns, inter alia, relationships with terms such as subordination or working time. The article puts forward a thesis of possible broader understanding of the concept of the time of contract performance. This will create an option to extend this concept also to the legal relations not covered yet by protection in the context of their performance time.